2022
DOI: 10.3390/textiles2010009
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Physical and Mechanical Properties of Polyacrylonitrile Nanofibers Reinforced with Succinite and Silicon Dioxide Nanoparticles

Abstract: In this research, we focused on testing the physical and mechanical properties of the developed polyacrylonitrile (PAN) composite nanofibers with succinite (Baltic amber) and SiO2 particles using standard methods of nanofiber testing (physical and mechanical properties). Polyacrylonitrile composite nanofibers (based on the electrospinning method) were coated on an aluminum substrate for structural investigation. SEM was used to determine the average fiber diameter and standard deviation. The mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Studies based on nanofibers have revealed that the mechanical characteristics grow exponentially as the fiber diameter drops to a critical point. When the nanofibers are intertwined, the nanofiber’s structure has fewer irregularities and a more uniform structure, resulting in increased endurance [ 21 , 50 , 51 , 52 , 53 ]. In our research, we found that when nanofibers were collected at 1800 rpm with an average diameter of 234.85 ± 43.68 nm, the young’s modulus was 3200 ± 15, which was higher than when the nanofibers were collected at a lower speed or on a flat plate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies based on nanofibers have revealed that the mechanical characteristics grow exponentially as the fiber diameter drops to a critical point. When the nanofibers are intertwined, the nanofiber’s structure has fewer irregularities and a more uniform structure, resulting in increased endurance [ 21 , 50 , 51 , 52 , 53 ]. In our research, we found that when nanofibers were collected at 1800 rpm with an average diameter of 234.85 ± 43.68 nm, the young’s modulus was 3200 ± 15, which was higher than when the nanofibers were collected at a lower speed or on a flat plate.…”
Section: Resultsmentioning
confidence: 99%
“…There are several methods for producing nanofibers, including jet blowing, melt blowing, coextrusion, interfacial polymerization, and electrospinning [ 18 , 19 , 20 ]. Among these approaches, electrospinning has been extensively used to create polymer nanofibers, nanocomposites, as well as nanofibers containing different nanoparticles [ 21 , 22 , 23 , 24 ], graphene [ 25 ], graphene oxide [ 26 ], and carbon nanotubes [ 27 ] for different applications, such as biomedical [ 28 , 29 ], energy conversation [ 30 ], and tissue engineering [ 31 , 32 ]. Furthermore, the use of an electrospun thermoplastic nanofiber mats to toughen the glass/carbon epoxy laminated composites without degrading the in-plane mechanical properties and without considerably increasing the laminate thickness and weight has emerged as a promising technology [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these are the polymer solution's molecular weight, volume, solution flow rate, viscosity, conductivity, surface tension, syringe-to-collector distance, ambient temperature, and humidity [7]. Nanofibers' strength increases as their diameter decreases [8]. In addition, highly oriented, flexible nanofibers with exceptional mechanical properties are in extremely popular for several applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…The attracting features of PAN such as low density, thermal stability, and high tensile strength make PAN an important material in various fields including automobile sector, textile, high temperature industrial plants, and so on. [9,10] Recently, PAN (as tribopositive) and polyvinyl butyral (PVB) were used as contact material for triboelectrification by Yar et al [11] In their experiments zinc oxide (ZnO) and boric acid (B(OH)3) were added to study their influence in the device's performance. No favorable output was obtained for ZnO while for the PAN/B(OH) 3 TENG, the enhanced power output was around 6.67 W m −2 .…”
Section: Introductionmentioning
confidence: 99%